Forward Premium Anomaly and Risk Premiums in the Currency Markets: A Literature Review - Kumar, Satish; Pathak, Rajesh; Ranajee (Indian Journal of Finance, 2014)
The uncovered interest rate parity (UIP) is one of the most important theories explaining the relationship between the currency spot and futures rate. UIP states that under the assumption of rational expectations, the futures rate should be an unbiased predictor of the future spot rate. However, there is a vast literature that suggests that the UIP is empirically violated, and this condition is called forward premium anomaly. The forward premium anomaly is a condition when the forward rate is not an unbiased predictor of the future spot rate. One of the main reasons for the forward premium anomaly has been attributed to the presence of time-varying risk premiums. Prior studies have not been successful in addressing the issue of forward premium anomaly in the currency markets. In this paper, we presented an overview of the existing literature which explains the forward premium anomaly and the risk premium.